TIPE KEPRIBADIAN BIG FIVE DAN KONFLIK ANTARA PEKERJAAN-KELUARGA PERAWAT - Rismi Darmia; Lukman Nadjamuddin; Nur Afni Indahari (Jurnal Psikologi TALENTA, 2018)
The purpose of this study was to determine the relationship between the big five personality types (extraversion, agreableness, neuroticism, conscientiousness, openness to experience) and work-family conflict on women nurses. Subjects in this study were female nurses who have been married and have children in the Makassar Police Hospitals 75 people. Based on the results of data analysis showed that there was no correlation between extraversion with work-family conflict on women's care, p=0,175, with correlation coefficient, r = -0.158. There is no correlation between a greableness with work-family conflict in nurses woman (p=0,052) with a correlation coefficient (r = -0.225). There was a negative relationship between conscientiousness factor with work-family conflict on women's care with work-family conflict on women's care with correlation coefficient (r = - 0.321) and (p = 0.004). Neuroticism factors positively associated with work-family conflict on women's care with correlation coefficient (r = 0.330) and (p = 0.869). Factors openness to experience is not related to the work-family conflict female nurses with a correlation coefficient (r = - 0.019) and conscientiousness with work-family conflict on women’s care.